Excessive Salt Intake Among Hypertensive Patients in Nepal: A Multicenter Observational Study - Acharya, Suman; Shrestha, Suraj; Kharel, Sanjeev; Neupane, Ashru; Khadka, Naresh Bahadur; Bhattarai, Anjan; Sigdel, Mahesh Raj; Singh, Dibya (Nepalese Heart Journal, 2026)
Background and Aims: Dietary salt is a modifiable risk factor for hypertension and cardiovascular diseases. The World Health Organisation recommends salt restriction to <5 grams/day, while Nepalese are consuming almost twice the recommended amount of salt. 24-hour urine sodium excretion is the gold standard measure of daily salt intake. However, various equations (eg. INTERSALT, Kawasaki) are used to derive salt intake from spot urine samples. This study aimed to assess dietary salt intake among patients with hypertension and its relationship with blood pressure. Methodology: This is a cross-sectional, observational, multi-centre study among hypertensive patients who came to the medical OPD of Tribhuvan University Teaching Hospital and Manmohan Cardiothoracic Vascular and Transplant Centre. Random spot urine sodium, and creatinine were tested to estimate daily salt intake using the INTERSALT and the Kawasaki equation. Results: A total of 222 participants (M = 95, F = 127) were enrolled in the study, with a mean systolic and diastolic blood pressure of 132.46 mmHg and 78.36 mmHg, respectively. Notably, 40.99% of participants had uncontrolled blood pressure. Average daily salt intake was 10.27 ± 2.60 grams and 10.31 ± 5.01 grams using the INTERSALT equation and the Kawasaki equation. About 97.1% were consuming higher than the recommended amount. Salt intake had a weak positive correlation with systolic blood pressure (r = 0.266; p < 0.001). Conclusions: Participants were consuming twice the recommended amount of salt daily and had poor blood pressure control.